Pengaruh Kebijakan Harga, Citra Merek, dan Kualitas Produk terhadap Kepuasan Pelanggan Telkomsel - Ila, Nurfadilah; Dg. Parani, Syamsul Bahri; Adam, Rosida P.; Palawa, Muh. Riswandi (Jurnal Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This study aims to analyze the influence of price policy, brand image, and product quality on customer satisfaction among Telkomsel card users in Palu City. Research Methodology: This study used a quantitative approach with non-probability sampling, specifically purposive sampling, involving 120 respondents. Data were collected through questionnaires using a Likert scale and analyzed using SPSS version 30. Results: Price policy, brand image, and product quality each had a significant partial effect on customer satisfaction. Simultaneously, all the independent variables significantly influenced customer satisfaction. Conclusion: The study concludes that improving price policies, strengthening brand image, and ensuring consistent product quality are essential strategies for enhancing customer satisfaction. Companies that prioritize these aspects are more likely to build stronger customer loyalty and maintain their competitiveness in the telecommunications industry. Limitations: This study only examined price policy, brand image, and product quality, while other factors potentially affecting customer satisfaction were not analyzed. Additionally, the research was conducted only in Palu City, which limited its scope. Contribution: This study demonstrates that price policy, brand image, and product quality significantly affect customer satisfaction. The findings can assist companies in formulating effective strategies and serve as a reference for future studies.